Black whiteness : Admiral Byrd alone in the Antarctic - Burleigh, Robert; Krudop, Walter, 1966- (New York : Atheneum Books for Young Readers, 1998)
An account of Admiral Richard Byrd's stay alone in a small shack during an Antarctic winter.
3.5
3-6
3-6
Wilson's Children
Elem. School Library Collection
School Library Journal
Keywords: Byrd, Richard Evelyn, -- 1888-1957 -- Juvenile literature; Byrd, Richard Evelyn, -- 1888-1957.; Byrd, Richard Evelyn, -- 1888-1957.; Explorers -- United States -- Juvenile literature; Explorers; Explorers; Antarctica -- Discovery and exploration -- Juvenile literature; Antarctica -- Discovery and exploration; Antarctica -- Exploration